The Lexicographic Treatment of Ideophones in Zulu - de Schryver, Gilles-Maurice (Lexikos, 2009)
Abstract: The ideophone, a word class not unique to but highly characteristic of the Bantu languages, presents particular challenges in both monolingual and bilingual lexicography. Not only is this part of speech without a counterpart in most other languages, the meaning of ideophones is highly elusive. In this research article these challenges are studied by means of an analysis of the treatment of ideophones in a corpus-driven Zulu–English school dictionary project. Keywords: LEXICOGRAPHY, DICTIONARY, BILINGUAL, CORPUS, FREQUENCY, BANTU, ZULU (ISIZULU), ENGLISH, IDEOPHONE, SEMANTIC IMPORT, PARAPHRASE, PART-OF-SPEECH MISMATCH Samenvatting: De lexicografische behandeling van ideofonen in Zoeloe. De ideofoon, een woordklasse die niet uniek maar wel heel karakteristiek is voor de Bantoetalen, is een echte uitdaging in zowel de monolinguale als bilinguale lexicografie. Niet enkel heeft deze woordklasse geen equivalent in de meeste andere talen, de betekenis van ideofonen is heel moeilijk vast te leggen. In dit onderzoeksartikel worden deze uitdagingen onderzocht aan de hand van een analyse van de behandeling van ideofonen in een corpus-gedreven Zoeloe–Engels schoolwoorden-boekproject. Sleutelwoorden: LEXICOGRAFIE, WOORDENBOEK, TWEETALIG, CORPUS, FRE-QUENTIE, BANTOE, ZOELOE, ENGELS, IDEOFOON, SEMANTISCHE LADING, PARAFRASE, VLOEKENDE WOORDKLASSEN